2015
DOI: 10.1002/cncr.29833
|View full text |Cite
|
Sign up to set email alerts
|

Acute respiratory infections in children and adolescents with acute lymphoblastic leukemia

Abstract: Background Knowledge about the incidence, clinical course and impact of respiratory viral infections in children with acute lymphoblastic leukemia (ALL) is limited. Methods A retrospective cohort of patients with newly diagnosed ALL on Total Therapy XVI protocol at St Jude Children’s Research Hospital between 2007 and 2011 was evaluated. Results Of 223 children, 95 (43%) developed 133 episodes of viral acute respiratory illness (ARI) (incidence = 1.1/1,000 patient-days). ARI without viral etiology was iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
57
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(62 citation statements)
references
References 21 publications
1
57
1
3
Order By: Relevance
“…Influenza is suggested to be a frequent pathogen of URTI both in immunocompetent and immunocompromised children. 14,15 In our series of children with cancer, HRV was found to be the most frequent (24.3%) viral respiratory tract infection pathogen. However, in most published series on pediatric cancer, HRV has not been included in the viral panel.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Influenza is suggested to be a frequent pathogen of URTI both in immunocompetent and immunocompromised children. 14,15 In our series of children with cancer, HRV was found to be the most frequent (24.3%) viral respiratory tract infection pathogen. However, in most published series on pediatric cancer, HRV has not been included in the viral panel.…”
Section: Discussionmentioning
confidence: 74%
“…However, in most published series on pediatric cancer, HRV has not been included in the viral panel. 14,16 The high incidence of HRV can also be attributed to the inclusion of HRV in the diagnostic testing panels during recent years, which has led to similar cases. [17][18][19][20][21] In the present study, no seasonal differences were observed in the incidence of HRV infection; similarly, certain past studies have also reported the absence of any seasonal differences.…”
Section: Discussionmentioning
confidence: 99%
“…Historically, research has focused on identifying pulmonary‐toxic therapies, such as radiation and hematopoietic stem cell transplant (HSCT), to inform risk‐based pulmonary follow‐up . However, respiratory infections are also a significant cause of pulmonary morbidity during treatment . In particular, recent studies using polymerase chain reaction (PCR) diagnostics have found respiratory viral infections (RVI) cause up to 57% of febrile episodes, and that children undergoing chemotherapy are at risk of more severe RVIs with a prolonged clinical course and higher viral loads …”
Section: Introductionmentioning
confidence: 99%
“…Second to rhinovirus, the most represented virus is HRSV, found in 2.1-46% of cases. HMPV has been found in 3.3-13.5% of cases, being classified as the third [19], fourth [18,[20][21][22][23], fifth [24] and tenth [25,26] most frequent respiratory virus, according to the literature reviewed. Interestingly, HMPV has been reported as the only viral agent that was responsible for an outbreak in a pediatric oncology population [27] (Table 1).…”
Section: Distribution Of Respiratory Viruses In Pediatric Cancermentioning
confidence: 99%